The Effect of Ownership Structure on Financial Performance in Lippo Group Company - Ristati; Raihan Cahaya; Nurlela; Ghazali Syamni; Zulham Ibrahim (CV. Literasi Indonesia, 2021)
This study examined the effect of Ownership Structure on Financial Performance at Lippo Group companies in Indonesia from 2015 to 2019. The number of samples in this study was 14 companies and 60 observations. The data were accessed on www.idx.go.id. The data used in this study was panel data or a combination of cross-section data and time-series data. The data analysis method in this research was the Panel Data Regression analysis method with panel estimation model Random Effect Model. The results showed that Managerial ownership and institutional ownership had a negative and significant effect on financial performance.